Socio-economic Analysis of the Songkhla Economy - Hari Sharma Neupane (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The study site — Songkhla province is playing a vital role for economic and social development in the Southern Thailand being an international marketing hub for natural rubber and other agricultural products. In this context, this academic work provides analytical essays focusing on poverty and income inequality; tourism business; natural rubber production and marketing, and glimpse of Songkhla’s economy.